Reflections on out-of-home media in preserved landscapes - Baungratz, Liriane; Casarin, Vanessa (InfoDesign, 2024)
This article presents an investigation on outdoor advertising in protected historical centers, where urban landscapes highlight symbolic, sentimental, and cultural references. The aim is to evaluate outdoor advertising installed within buildings and the perception of different users. A geographical focus was established within the context of the Heritage Site of Laguna/SC. The qualitative and exploratory research involved field surveys and interviews, totaling 41 participants. Regarding the field survey, it was evident that due to the restrictiveness of the existing guidelines in the area, few commercial establishments comply with the regulations. As for the content analysis used for processing interview data, it revealed both agreements and disagreements in the discourse among different interviewee groups and within individuals of the same sample group.